Communication dynamics in farmer groups: Enhancing food security programs through agricultural collaboration - Mulyasara, Anis (Holistic: Journal of Tropical Agriculture Sciences, 2025)
Background: Bungaraya Subdistrict is one of the largest rice-producing areas in Riau Province. However, in 2023, rice production experienced a significant decline, decreasing from the target of 45,463 tons to 26,064 tons. This decline highlights the necessity of supporting food security programs implemented by farmer groups (Gapoktan). Communication dynamics within Gapoktan play a crucial role in supporting food security initiatives. This study examines the communication dynamics within Gapoktan Sumber Rezeki, focusing on how these dynamics contribute to the success of food security programs. Methods: This research employs a descriptive qualitative approach, involving seven informants as participants. Data collection methods include interviews, observations, and document analysis to gain a comprehensive understanding of communication dynamics within Gapoktan Sumber Rezeki. The study categorizes communication dynamics into two types: formal and informal communication, further distinguishing between vertical and horizontal communication structures. Findings: The findings reveal that communication dynamics within Gapoktan Sumber Rezeki are divided into formal and informal communication. Formal communication occ urs through both vertical and horizontal channels. Vertical communication involves exchanges between the Gapoktan members and Agricultural Extension Workers (PPL), facilitating the dissemination of program information, policy coordination, and activity management. Horizontal communication occurs among members of similar levels within the organization, utilizing face-to-face meetings and WhatsApp groups. Informal communication, on the other hand, takes place during casual interactions in the field, such as discussions and information sharing about rice cultivation. This informal interaction fosters stronger relationships, trust, and collaboration among members. Conclusions: Overall, both formal and informal communication significantly support food security programs by enhancing coordination, transparency, and solidarity within the group. Novelty/Originality of this article: By examining both vertical and horizontal communication structures, the research highlights the critical role of structured and casual communication in achieving organizational goals.